The Federal Democratic Republic of Ethiopia : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Ethiopia showed commendable performance under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors appreciated this development, and emphasized the need to strengthen fiscal and monetary policies, enhance revenues, strengthen public expenditure management, and introduce poverty-related activities. They welcomed the restructuring plan for the Commercial Bank of Ethiopia, and stressed the need to strengthen the organizational structure and finances of the National Bank of Ethiopia. They agreed that Ethiopia has successfully completed the fifth review under the PRGF program, and approved further financial assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet